2014
DOI: 10.1210/jc.2014-2080
|View full text |Cite|
|
Sign up to set email alerts
|

Sex Differences in Biomarkers Associated With Insulin Resistance in Obese Adolescents: Metabolomic Profiling and Principal Components Analysis

Abstract: Objective Obesity and insulin resistance (IR) predispose to type 2 diabetes mellitus. Yet only half of obese adolescents have IR and far fewer progress to type 2 diabetes mellitus. We hypothesized that amino acid and fatty acid metabolites may serve as biomarkers or determinants of IR in obese teens. Research Design and Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
105
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 40 publications
15
105
2
2
Order By: Relevance
“…There are several studies showing similar results as our study concerning the sex differences in metabolites [3, 15, 17]. However, to our knowledge there is only one other study that has examined sex differences with respect to HC use and metabolomics or that has investigated associations between metabolomics with different components of the MetS [3, 15]. Given a significant number of women of childbearing age are taking HC, this is a large group that is not represented or analysed in many clinical studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There are several studies showing similar results as our study concerning the sex differences in metabolites [3, 15, 17]. However, to our knowledge there is only one other study that has examined sex differences with respect to HC use and metabolomics or that has investigated associations between metabolomics with different components of the MetS [3, 15]. Given a significant number of women of childbearing age are taking HC, this is a large group that is not represented or analysed in many clinical studies.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the metabolomics studies conducted to date have either not taken potential sex differences into account or have used males and females in the same model. There are several studies showing similar results as our study concerning the sex differences in metabolites [3, 15, 17]. However, to our knowledge there is only one other study that has examined sex differences with respect to HC use and metabolomics or that has investigated associations between metabolomics with different components of the MetS [3, 15].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Findings in pediatric cohorts have been inconsistent (Frohnert and Rewers, 2016). Thus, two studies showed a positive correlation between BCAA, BMI and HOMA-IR (Newbern et al, 2014; Perng et al, 2014), and another an association with obesity (McCormack et al, 2013), but still others found no significant differences in BCAA levels in normal weight compared to obese adolescents (Wahl et al, 2012), and even a positive correlation between BCAA/BCAA metabolites and insulin sensitivity (Si) (Michaliszyn, et al, 2012). However, in a group of 17 pre- or early-pubertal children (age 8–13 years), baseline BCAA levels were found to be associated with HOMA-IR measured 18 months later, suggesting that, as in adults, BCAA levels may be predictive of future disease risk in adolescent subjects (McCormack et al, 2013).…”
Section: Metabolomics Reveals Associations Of Metabolites With Cardiomentioning
confidence: 99%
“…For diagnostic use, changes in the concentration of amino acids in blood plasma and urine are used as an index of many diseases, such as an inborn error of amino acid metabolism, [1][2][3] liver disease, 4 renal disease, 5 and endocrine disease. 6 In addition, 17 kinds of proteinogenic amino acids are targeted for amino acid composition analysis or accurate quantification of protein/peptide. [7][8][9][10][11][12][13][14][15] In these methods, the constituent amino acids released from the original protein/ peptide through hydrolysis are quantified.…”
Section: Introductionmentioning
confidence: 99%